The reason for the patient choosing UMM hospital - Riskiyah Riskiyah (Journal of Management and Business, 2021)
Hospital is one of the places choosen by people who seek medical treatment when they get sick. One of the main reasons people choose a hospital is when they feel satisfied with the hospital services. The University of Muhammadiyah Malang (UMM) Hospital is classified as a new hospital that complies with the standard released by The Indonesian Health Department in term of Bed Occupancy Rate. The aim of this study is to find out the reasons behind patients' decision making on choosing medical services at UMM Hospital. A qualitative phenomenology method was used in this study. Data collection was conducted in February until March 2016. Interview was conducted to 8 informants that represent the patients from VIP class, class I, class II and class III of UMM Hospital. They are five themes about patient decision making on why they choose UMM Hospital as a health care provider such as the location, receives BPJS, friends recommendation, no other choice, and UMM Hospital is the best option. In conclusion, the patient’s decision making to choose hospitalization at UMM Hospital was influenced by several things. The existence of this information can be input for hospitals in developing appropriate marketing strategies and can further improve the quality of service to the community.